SAT-LB043 Elevated Testosterone Exposure Affects Ciliary Function and Gene Expression in the Human Fallopian Tube - Jackson-Bey, Tia (J Endocr Soc, 2019)
Hyperandrogenism, oligo- or anovulation, and polycystic appearing ovaries on ultrasound are the clinical hallmarks of polycystic ovarian syndrome (PCOS), the most common endocrinopathy of reproductive aged women. Women living with PCOS are at increased risk for metabolic disorders, such as metabolic syndrome and diabetes mellitus, cardiovascular disease, and hormonally-sensitive neoplasia such as endometrial cancer, throughout the lifespan. However, the condition is most commonly diagnosed during the reproductive years when menstrual irregularities and infertility become bothersome for many affected women. Hyperandrogenism remains one of the most prominent features of PCOS and is marked by increased serum levels of androgens, including testosterone. The fallopian tube is the site of gamete transport, fertilization and early embryogenesis in humans, and is thus essential in natural reproduction. Cilia, small hair-like projections which line the fallopian tube epithelium, play a major role in facilitating embryo transport through the fallopian tube to the uterus. The impact of elevated testosterone on the human fallopian tube epithelium has not been fully investigated and is of interest in understanding the pathophysiology of infertility in the PCOS population. To study the impact of elevated testosterone on fallopian tube epithelium, we exposed human fallopian tube epithelium to either a hormonally physiologic or hyperandrogenic culture media for 14 days. The hyperandrogenic media was characterized by elevated testosterone concentration of 2nM, compared to 0.8 nM in the physiologic media. After 7 days, a difference was seen in the rate of ciliary beating frequency (CBF), favoring the physiologic controls as detected by spinning disk confocal microscopy. Changes in genes that regulate cilia structure and function were found after 14 days. RNA sequencing data showed that amongst other genes, FOXJ1, SAA2, and DNAH5 were downregulated and KIF5C, MAP2 and NTN4 were upregulated respectively in the hyperandrogenic group. Immunohistochemistry staining confirmed that ciliary protein levels also were altered in the human fallopian tube epithelium exposed to elevated testosterone and will further be used to validate additional changes seen by the RNAseq. These preliminary findings suggest a that elevated testosterone may have an impact on cilia expression and function in the human fallopian tube. These results could add to the mechanisms of infertility and subfertility in women with PCOS and may reinvigorate clinical studies in the effect of decreasing serum testosterone in women with hyperandrogenic PCOS who are seeking infertility care, those who are unsuccessful in first line infertility treatments or in women in whom in vitro fertilization (IVF) is not available or unaffordable. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.